Analysis of key components of the “Digital University” Model - I. N. Golyshkova (State University of Management, 2020)
One of the priorities of the government program “Digital economy of the Russian Federation” is the progressive development of the existing education system, which should provide the economy with competent personnel. In addition, this Program declares the need to create a system of motivation for the development of the necessary competencies and participation of personnel in the development of the digital economy of Russia. On the other hand, the current educational trends both in Russia and abroad require the creation of a fundamentally new, open education system aimed not only at creating future competencies, but also at expanding the availability of education. Access to education in this case implies the possibility of obtaining educational services for all categories of citizens, including residents of remote regions, as well as for people with disabilities. Currently actively developing online course platforms (Massive Open Online Courses) do not yet provide a full range of educational services in addition online students do not have the opportunity to obtain a higher education diploma, which would be recognized by employers. Accordingly, the task of providing modern, accessible and open educational services still falls on classical universities. All this requires transformation of the classical educational system, which ultimately implies the creation of a “Digital University”. The author of the article presents her own view on the formation of the “Digital University” model and explains her point of view about the key elements of this model. The article substantiates and describes the five main components of the “Digital University” model and also concludes that further detailed description of these proposed components in their relationship with the processes of digital transformation of the University is necessary.